Identification of a Quorum Sensing System Regulating Capsule Polysaccharide Production and Biofilm Formation in Streptococcus zooepidemicus - Xie, Zhoujie; Meng, Kai; Yang, Xiaoli; Liu, Jie; Yu, Jie; Zheng, Chunyang; Cao, Wei; Liu, Hao (Frontiers in Cellular and Infection Microbiology, 2019)
Streptococcus zooepidemicus is an important opportunistic pathogen of several species including humans. This organism is also well known as the main producing strain in industrial production of hyaluronic acid (HA), which is the component of its capsule polysaccharide. How its virulence and capsule polysaccharide production is regulated remains poorly understood. Intercellular chemical signaling among bacteria provides communities of microbes the opportunity to coordinate gene expression to facilitate group behavior, such as pathogenicity, capsule polysaccharide production, etc. Yet no conserved cell-to-cell signaling system has been elucidated in S. zooepidemicus. Encoded within the genome of S. zooepidemicus is one Rgg regulator encoding gene (rgg) with low similarity to both rgg2 and rgg3 from Streptococcus pyogenes. A small ORF (named as shp) encoding a novel short hydrophobic peptide (SHP) was found in the vicinity of rgg. We found that the active form of pheromone is short and hydrophobic (LLLLKLA), corresponding to the C terminal 7 amino acids of the pre-peptide Shp, which shows divergent sequence to all peptide pheromones reported in streptococci. In response to active SHP, Rgg functions as a transcriptional activator to induce the expression of shp, forming a positive feedback circuit. Bacteria social behaviors, such as capsule polysaccharide production and biofilm formation, were significantly affected when the rgg-shp pathway was inactivated. These data provide the first demonstration that Rgg/Shp signaling pathway comprises an active quorum sensing system in S. zooepidemicus.